In silico screening of phenylethanoid glycosides, a class of pharmacologically active compounds as natural inhibitors of SARS-CoV-2 proteases - Caio Felipe de Araujo Ribas Cheohen; Maria Eduarda Alves Esteves; Thamirys Silva da Fonseca; Carla Monteiro Leal; Fernanda de Lemos Fernandes Assis; Mariana Freire Campos; Raianne Soares Rebelo; Diego Allonso; Gilda Guimarães Leitão; Manuela Leal da Silva; Suzana Guimarães Leitão (Computational and Structural Biotechnology Journal, 2023)
Since the advent of Covid-19, several natural products have been investigated regarding their in silico interactions with SARS-CoV-2 proteases ˗ 3CLpro and PLpro, two of the most important pharmacological targets for antiviral development. Phenylethanoid glycosides (PG) are a class of natural products present in important medicinal plants and a drug containing this group of active ingredients has been successfully used in the treatment of Covid-19 in China. Thus, a dataset with 567 derivatives of this class was built from reviews published between 1994 and 2020, and their interaction against both SARS-CoV-2 proteases was investigated. The virtual screening was performed by filtering the PGs through the evaluation of scores based on the AutoDock Vina, GOLD/ChemPLP, and GOLD/GoldScore evaluation functions. The bRO5 pharmacokinetic parameters of the PGs ranked in the previous step were analyzed and their interaction with key amino acid residues of the 3CLpro and PLpro enzymes was evaluated. Ninety-eight compounds were identified by computational approaches against PLpro and 80 PGs against 3CLpro. Of these, four interacted with key catalytic residues of PLpro, which is an indicative of inhibitory activity, and three compounds interacted with catalytic key residues of 3CLpro. Of these, five PGs occur in plants of the Traditional Chinese Medicine (TCM), while two are components of plants/formulations currently used in the Covid-19 protocols in China. The data presented here show the potential of PGs as selective inhibitors of SARS-CoV-2 3CLpro and PLpro.